Chemically strengthened glass and method for producing same
By chemically strengthening the specific molten salt composition for the chemical reinforcement glass with a plate thickness greater than 2mm, a specific stress distribution is formed, and the problem of insufficient fly stone resistance and safety in the prior art is solved, and better fly stone resistance and safety are achieved.
Patent Information
- Application Number
- CN202411165120.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-25
- Filing Date
- 2024-08-23
- Publication Date
- 2025-02-25
AI Technical Summary
When existing chemically reinforced glass improves fly stone resistance and safety, it may lead to excessive compression stress on the glass surface, causing the fragments to scatter when the glass breaks, posing a safety hazard.
By using a specific molten salt composition to chemically strengthen the glass with a plate thickness of more than 2 mm, a specific stress distribution is formed, and the fly stone resistance and safety are improved.
Chemically reinforced glass showing excellent flying stone resistance and safety is achieved, reducing the scratch area and depth of flying stone collisions, and preventing the scattering of fine fragments of the glass when it breaks.
Smart Images

Figure CN119504139A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to chemically strengthened glass and a method for producing the same. Background Art
[0002] Mobile devices such as cars, trains, and drones, or anti-theft devices such as outdoor sensors and surveillance cameras are equipped with multiple sensors with various functions.
[0003] As a material of the protection member for protecting the sensor, it is preferable to select a material having high transmittance for transmitting visible light and excellent strength.
[0004] As a protective member for protecting a sensor, a sensor module using glass is known. For example, Patent Document 1 discloses a sensor module using chemically strengthened glass as a protective member.
[0005] Chemically strengthened glass is obtained by chemically strengthening the glass (ion exchange treatment) by bringing the glass into contact with an inorganic salt composition such as sodium nitrate or potassium nitrate, thereby forming a compressive stress layer on the surface of the glass.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2019 / 009336 Summary of the invention
[0009] There are roughly three types of strength required for glass protecting the sensor.
[0010] The first is stone-flying resistance. When a sensor is mounted on a mobile device, foreign objects such as stones may collide with the sensor module during driving. If a momentary impact is applied from the outside due to the collision of stones, the stress at the time of the collision is not relaxed and concentrated stress is generated, which may damage the glass and sensor as protective components. Therefore, the glass protecting the sensor is required to have excellent stone-flying resistance.
[0011] The second is the falling ball impact strength (hereinafter also referred to as falling ball strength). The glass protecting the sensor needs to be strong enough not to break easily when an object collides with it or when the glass is dropped.
[0012] The third is scratch resistance against flying stones (hereinafter also referred to as scratch resistance). Scratches on the glass surface caused by collision with flying stones, etc., as well as cracks and deterioration in appearance caused by scratches, are problems, so scratch resistance that reduces the area and depth of scratches is required.
[0013] In order to improve the flying stone resistance, it is effective to form the compressive stress layer to a depth that is a certain ratio or more relative to the plate thickness.
[0014] However, if a chemical strengthening treatment is performed for a long time in order to form a compressive stress layer to a sufficient depth on a chemically strengthened glass having a plate thickness greater than 2 mm, there is a safety problem as follows: the total amount of compressive stress on the glass surface increases, and the CT also increases accordingly, resulting in exceeding the CT limit, and when breaking, the fragments become very small and scatter over a wide area.
[0015] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a chemically strengthened glass exhibiting excellent flystone resistance and safety, and a method for producing the same.
[0016] The present inventors have studied the above-mentioned problems and found that by using a specific molten salt composition to chemically strengthen a chemically strengthened glass having a plate thickness greater than 2 mm, a chemically strengthened glass having a specific stress profile can be obtained, thereby improving the flystone resistance and safety, thereby completing the present invention.
[0017] One embodiment of the present invention is as follows.
[0018] [1] A chemically strengthened glass having a plate thickness greater than 2 mm, a compressive stress layer depth DOC of 500 to 1500 μm, and a maximum tensile stress CTmax of 20 to 59 MPa.
[0019] [2] The chemically strengthened glass according to [1], wherein, when the plate thickness is t, the maximum value CTmax of the tensile stress is less than or equal to CTA calculated by the following formula (1), and the unit of t is mm.
[0020] CTA=-36.2ln(t)+97.7…(1)
[0021] [3] The chemically strengthened glass according to [1] or [2] above, wherein the surface compressive stress value CS0 is 1400 MPa or less.
[0022] [4] The chemically strengthened glass according to any one of [1] to [3], wherein the compressive stress value CS at a depth of 10 μm from the surface is 10 Below 200MPa.
[0023] [5] The chemically strengthened glass according to any one of [1] to [4], wherein the depth DOL at which the compressive stress value is 50 MPa 50 200~600μm.
[0024] [6] The chemically strengthened glass according to any one of [1] to [5], wherein the compressive stress value CS at a depth of 400 μm from the surface is 400 It is 30~100MPa.
[0025] [7] The chemically strengthened glass according to any one of [1] to [6], wherein the compressive stress value CS at a depth of 500 μm from the surface is 500 It is 15~80MPa.
[0026] [8] The chemically strengthened glass according to any one of [1] to [7], wherein the compressive stress value CS at a depth of 600 μm from the surface is 600 0~50MPa.
[0027] [9] The chemically strengthened glass according to any one of [1] to [8], wherein the compressive stress value CS at a depth of 400 μm from the surface is 400 The compressive stress value CS at a depth of 10 μm from the surface 10 CS 400 / CS 10 It is 0.30~0.80.
[0028]
[10] The chemically strengthened glass according to any one of [1] to [9], wherein the compressive stress value CS at a depth of 600 μm from the surface is 600 The compressive stress value CS at a depth of 10 μm from the surface 10 CS 600 / CS 10 It is 0.04~0.50.
[0029]
[11] The chemically strengthened glass according to any one of [1] to
[10] above, wherein the deep slope is -0.25 to -0.01.
[0030]
[12] The chemically strengthened glass according to any one of [1] to
[11] , wherein when the plate thickness is t, a ratio of the compressive stress layer depth DOC to 1000t (DOC / 1000t) is 0.15 to 0.30, and the unit of t is mm.
[0031]
[13] The chemically strengthened glass according to any one of [1] to
[12] , wherein the integral value ICS in the thickness direction of the compressive stress value from a depth of 400 μm to a depth position where the compressive stress value is zero is 400 It is 3000~60000MPa·μm.
[0032]
[14] The chemically strengthened glass according to any one of [1] to
[13] , wherein the integral value ICS in the thickness direction of the compressive stress value from a depth of 400 μm to a depth position where the compressive stress value is zero is 400The ratio ICS400 / ICS of the integrated value ICS of the compressive stress value in the plate thickness direction from the surface to the depth position where the compressive stress value is zero is 0.13 to 0.90.
[0033]
[15] The chemically strengthened glass according to any one of [1] to
[14] above, which is lithium-containing aluminosilicate glass.
[0034]
[16] The chemically strengthened glass according to any one of [1] to
[15] above, which contains 52 to 75% of SiO2, 1 to 20% of Al2O3, 1 to 20% of Na2O, and 1 to 20% of Li2O, expressed as mol% based on oxides.
[0035]
[17] The chemically strengthened glass according to any one of [1] to
[16] above, wherein the crack generation rate evaluated by the strength test method according to ISO 20567-1 Test Method A is 20% or less.
[0036]
[18] The chemically strengthened glass according to any one of [1] to
[17] above, wherein the crack generation rate evaluated according to the strength test method of SAE J400 is 20% or less.
[0037]
[19] The chemically strengthened glass according to any one of [1] to
[18] above, which is used as a protective member for an in-vehicle sensor.
[0038]
[20] A method for producing chemically strengthened glass, which is a method for producing the chemically strengthened glass described in any one of [1] to
[19] above, comprising bringing an inorganic salt composition containing a lithium inorganic salt in an amount of 0.1 mass % or more into contact with a chemically strengthened glass having a plate thickness greater than 2 mm.
[0039]
[21] The method for producing a chemically strengthened glass according to
[20] above, wherein the time for which the inorganic salt composition is in contact with the chemically strengthened glass is 25 hours or longer.
[0040]
[22] The method for producing a chemically strengthened glass according to
[20] or
[21] , wherein the chemically strengthened glass is preheated before the inorganic salt composition is brought into contact with the chemically strengthened glass.
[0041]
[23] The method for producing chemically strengthened glass according to any one of
[20] to
[22] above, wherein the content of lithium nitrate in the inorganic salt composition is 1% by mass or more, and the content of sodium nitrate is 80% by mass or more.
[0042] According to the present invention, a chemically strengthened glass exhibiting excellent flystone resistance and safety and a method for producing the same can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 (a) and (b) are perspective views showing a configuration example in which chemically strengthened glass is used as a protective member.
[0044] Figure 2 It is a schematic diagram for explaining the evaluation method of crack behavior.
[0045] Explanation of symbols
[0046] 1 Protective components
[0047] 2 Supporting part
[0048] 5 Installation
[0049] 10 cover
[0050] 20 Sensors
[0051] 30 Camera
[0052] 200 Chemically strengthened glass
[0053] 210 Chemically strengthened glass surface
[0054] 400 Test Bench
[0055] 410 Super Hard Automatic Punch
[0056] 411 Front end DETAILED DESCRIPTION
[0057] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments and can be implemented with arbitrary modifications within the scope not departing from the gist of the present invention.
[0058] In the present specification, “to” indicating a numerical range is used to mean that the numerical values described before and after it are included as the lower limit and the upper limit.
[0059] In this specification, unless otherwise specified, the composition of glass (the content of each component) is expressed as a mole percentage based on an oxide, and the mole percentage is simply expressed as "%".
[0060] In this specification, "substantially not containing" means that the content is lower than the level of impurities contained in raw materials, etc., that is, it is not intentionally added. Specifically, for example, it is less than 0.1%.
[0061] Hereinafter, "chemically strengthened glass" refers to glass subjected to a chemical strengthening treatment, and "glass for chemical strengthening" refers to glass before subjected to a chemical strengthening treatment.
[0062] In this specification, "stress distribution" refers to a graph showing the value of compressive stress with the depth from the glass surface as a variable. In the stress distribution, tensile stress is represented as a negative absolute value of compressive stress and positive value.
[0063] In this specification, the "depth of compressive stress layer (DOC)" refers to the depth from the glass surface to the position where the compressive stress value is zero (the distance from the surface).
[0064] In the following, the surface compressive stress value is sometimes referred to as CS0, and the compressive stress value at a depth of 10 μm from the surface is sometimes referred to as CS 10 , the compressive stress value at a depth of 50 μm from the surface is recorded as CS 50 , the compressive stress value at a depth of 400 μm from the surface is recorded as CS 400 , the compressive stress value at a depth of 500 μm from the surface is recorded as CS 500 , the compressive stress value at a depth of 600 μm from the surface is recorded as CS 600 .
[0065] The depth when the compressive stress value is 50 MPa is recorded as DOL 50 .
[0066] In addition, "tensile stress (CT)" refers to the tensile stress value at a depth of 1 / 2 of the plate thickness t.
[0067] <Method for measuring stress distribution>
[0068] In this specification, stress distribution measured by a scattered light photoelastic stress meter (SLP) and a glass surface stress meter (FSM) is used.
[0069] In this specification, unless otherwise specified, values such as compressive stress CS, tensile stress CT, and compressive stress layer depth DOC refer to values in the SLP stress distribution.
[0070] When two or more stages of chemical strengthening treatment are performed and an inorganic salt composition containing a potassium-containing inorganic salt (potassium ion) is used in the second stage of chemical strengthening treatment, the compressive stress value of the outermost surface of the chemically strengthened glass obtained at this time is the value measured by FSM.
[0071] As a method for measuring stress distribution using a scattered light photoelastic stress meter (SLP), the method described in International Publication No. 2018 / 056121 can be cited.
[0072] As a scattered light photoelastic stress meter (SLP), SLP-2000 manufactured by Orihara Manufacturing Co., Ltd. was used.
[0073] Other measurement conditions (software used, etc.) are described below.
[0074] As a method for measuring stress distribution using a glass surface stress meter (FSM), the methods described in International Publication No. 2018 / 056121 and International Publication No. 2017 / 115811 can be cited.
[0075] As a glass surface stress meter (FSM), FSM6000-UV manufactured by Orihara Manufacturing Co., Ltd. was used.
[0076] Hereinafter, each embodiment will be described.
[0077] <Chemically strengthened glass>
[0078] <<First embodiment>>
[0079] The chemically strengthened glass according to the first embodiment is preferably lithium-containing aluminosilicate glass.
[0080] The preferred composition of the lithium-containing aluminosilicate glass preferably contains 52 to 75% of SiO2, 1 to 20% of Al2O3, 1 to 20% of Na2O, and 1 to 20% of Li2O, expressed in mol% based on oxides.
[0081] More preferably, the chemically strengthened glass contains, expressed in mol % based on oxides, 52 to 75% SiO2, 1 to 20% Al2O3, 1 to 20% Li2O, 1 to 20% Na2O, 0 to 5% K2O, 0 to 20% MgO, 0 to 20% CaO, 0 to 20% SrO, 0 to 20% BaO, 0 to 20% ZnO, 0 to 1% TiO2, 0 to 8% ZrO2, and 0 to 5% Y2O3.
[0082] <<Second embodiment>>
[0083] The chemically strengthened glass of the second embodiment is preferably a crystalline glass. A preferred composition of the crystalline glass is preferably a composition containing 40 to 70% SiO2, 10 to 35% Li2O, and 1 to 15% Al2O3 expressed in mole % based on oxides.
[0084] More preferably, the chemically strengthened glass contains, expressed in molar % based on oxides, 40 to 70% SiO2, 10 to 35% Li2O, 1 to 15% Al2O3, 0.5 to 5% P2O5, 0.5 to 5% ZrO2, 0 to 10% B2O3, 0 to 10% Na2O, 0 to 5% K2O, and 0 to 4% SnO2.
[0085] <<Glass composition>>
[0086] Hereinafter, a preferred glass composition will be described.
[0087] <<<SiO2>>>
[0088] In the chemically strengthened glass of the first embodiment, SiO2 is a component that forms a network structure of the glass. In addition, it is a component that improves chemical durability. The content of SiO2 is preferably 52% or more, more preferably 56% or more, further preferably 60% or more, and particularly preferably 64% or more.
[0089] On the other hand, in order to improve the meltability, the SiO2 content is preferably 75% or less, more preferably 73% or less, further preferably 71% or less, and particularly preferably 69% or less.
[0090] In the chemically strengthened glass of the second embodiment, the content of SiO2 is preferably 40% or more, more preferably 45% or more, further preferably 48% or more, further preferably 50% or more, particularly preferably 52% or more, and most preferably 54% or more.
[0091] On the other hand, in order to improve the meltability, the SiO2 content is preferably 70% or less, more preferably 68% or less, further preferably 66% or less, and particularly preferably 64% or less.
[0092] <<<Al2O3>>>
[0093] In the chemically strengthened glass of the first embodiment, Al2O3 is an essential component for increasing the surface compressive stress generated by chemical strengthening. The content of Al2O3 is preferably 1% or more, more preferably 2% or more, further preferably 4% or more, and particularly preferably 6% or more.
[0094] On the other hand, in order to prevent the devitrification temperature of the glass from being too high, the Al2O3 content is preferably 20% or less, more preferably 18% or less, further preferably 17% or less, 16% or less, and particularly preferably 15% or less.
[0095] In the chemically strengthened glass of the second embodiment, the content of Al2O3 is preferably 1% or more, more preferably 2% or more, further preferably 3% or more, 5% or more, 5.5% or more, 6% or more, particularly preferably 6.5% or more, and most preferably 7% or more.
[0096] On the other hand, in order to prevent the devitrification temperature of the glass from being too high, the Al2O3 content is preferably 15% or less, more preferably 12% or less, further preferably 10% or less, particularly preferably 9% or less, and most preferably 8% or less.
[0097] <<<Na2O>>>
[0098] In the chemically strengthened glass of the first embodiment, Na2O is a component that improves the solubility of the glass and forms surface compressive stress by ion exchange. The content of Na2O is preferably 1% or more, more preferably 2% or more, and further preferably 4% or more.
[0099] If Na2O is too much, the chemical strengthening characteristics decrease, so the content of Na2O is preferably 20% or less, more preferably 18% or less, further preferably 16% or less, and particularly preferably 14% or less.
[0100] In the chemically strengthened glass according to the second embodiment, Na 2 O is not essential, but when contained, the content is preferably 0.5% or more, more preferably 1% or more, and further preferably 2% or more.
[0101] If there is too much Na2O, crystals such as Li3PO4, which serve as the main crystal, will not precipitate easily, or the chemical strengthening properties will decrease. Therefore, the Na2O content is preferably less than 10%, more preferably less than 9%, further preferably less than 8%, particularly preferably less than 7%, and most preferably less than 3%.
[0102] <<<K2O>>>
[0103] In the chemically strengthened glass according to the first embodiment, K 2 O, like Na 2 O, is a component that lowers the melting temperature of the glass and forms surface compressive stress by ion exchange.
[0104] When K2O is contained, the content is preferably 0.1% or more, more preferably 0.3% or more, further preferably 0.4% or more, particularly preferably 0.5% or more.
[0105] If K2O is too much, the chemical strengthening characteristics decrease or the chemical durability decreases, so it is preferably 5% or less, more preferably 4.8% or less, further preferably 4.5% or less, particularly preferably 4.2% or less, and most preferably 4.0% or less.
[0106] In the chemically strengthened glass according to the second embodiment, when K2O is contained, the content is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, and particularly preferably 2% or more.
[0107] If K2O is too much, the chemical strengthening characteristics decrease or the chemical durability decreases, so it is preferably 5% or less, more preferably 4% or less, further preferably 3% or less, particularly preferably 2% or less, and most preferably 1% or less.
[0108] <<<Na2O+K2O>>>
[0109] In the chemically strengthened glass of the first embodiment, from the viewpoint of improving the solubility of glass raw materials and forming surface compressive stress by ion exchange, the total content of Na2O and K2O (Na2O+K2O) is preferably 1% or more, more preferably 2% or more.
[0110] In the chemically strengthened glass according to the second embodiment, in order to improve the solubility of glass raw materials, the total content of Na 2 O and K 2 O, Na 2 O + K 2 O, is preferably 1% or more, more preferably 2% or more.
[0111] <<<Li2O>>>
[0112] In the chemically strengthened glass of the first embodiment, Li2O is a component that forms surface compressive stress by ion exchange. When Li2O is contained, its content is preferably 1% or more, more preferably 2% or more, further preferably 4% or more, and particularly preferably 5% or more.
[0113] On the other hand, in order to stabilize the glass, the content of Li2O is preferably 20% or less, more preferably 17% or less, further preferably 16% or less, and particularly preferably 15% or less.
[0114] In the chemically strengthened glass of the second embodiment, the content of Li2O is preferably 10% or more, more preferably 14% or more, further preferably 15% or more, further preferably 18% or more, particularly preferably 20% or more, and most preferably 22% or more.
[0115] On the other hand, in order to stabilize the glass, the Li2O content is preferably 35% or less, more preferably 32% or less, further preferably 30% or less, particularly preferably 28% or less, and most preferably 26% or less.
[0116] <<<K2O / R2O>>>
[0117] In the chemically strengthened glass of the first embodiment, if the ratio K2O / R2O of the K2O content to the total content of Li2O, Na2O and K2O (hereinafter referred to as R2O) is 0.2 or less, chemical strengthening characteristics can be improved and chemical durability can be improved, which is preferred.
[0118] K2O / R2O is more preferably 0.15 or less, and further preferably 0.10 or less. It should be noted that R2O is preferably 10% or more, more preferably 12% or more, and further preferably 15% or more. In addition, R2O is preferably 20% or less, and further preferably 18% or less.
[0119] In the chemically strengthened glass of the second embodiment, if the ratio K2O / R2O of the K2O content to the total content of Li2O, Na2O and K2O (hereinafter referred to as R2O) is 0.2 or less, chemical strengthening characteristics can be improved and chemical durability can be improved, which is preferred.
[0120] K2O / R2O is more preferably 0.15 or less, and further preferably 0.10 or less. It should be noted that R2O is preferably 10% or more, more preferably 15% or more, and further preferably 20% or more. In addition, R2O is preferably 29% or less, and further preferably 26% or less.
[0121] <<<MgO>>>
[0122] MgO is a component that stabilizes glass and improves mechanical strength and chemical resistance, so it is preferably contained when the Al2O3 content is low. The content of MgO is preferably 1% or more, more preferably 2% or more, further preferably 3% or more, and particularly preferably 4% or more.
[0123] On the other hand, if MgO is excessively added, the viscosity of the glass decreases, and devitrification or phase separation is likely to occur. The MgO content is preferably 20% or less, more preferably 19% or less, further preferably 18% or less, and particularly preferably 17% or less.
[0124] CaO, SrO, BaO, and ZnO are components that improve the solubility of glass and may be contained.
[0125] <<<CaO>>>
[0126] CaO is a component that improves the meltability of glass and improves the crushability of chemically strengthened glass, and may be contained. When CaO is contained, the content is preferably 0.5% or more, more preferably 1% or more, further preferably 2% or more, particularly preferably 3% or more, and most preferably 5% or more.
[0127] On the other hand, if the CaO content is too high, the ion exchange performance will significantly decrease, so it is preferably 20% or less. The CaO content is more preferably 14% or less, and further preferably 10% or less, 8% or less, 6% or less, 3% or less, and 1% or less in stages as follows.
[0128] <<<SrO>>>
[0129] SrO is a component that improves the meltability of glass and improves the crushability of chemically strengthened glass, and may be contained. When SrO is contained, the content is preferably 0.5% or more, more preferably 1% or more, further preferably 2% or more, particularly preferably 3% or more, and most preferably 5% or more.
[0130] On the other hand, if the SrO content is too high, the ion exchange performance will significantly decrease, so it is preferably 20% or less. The SrO content is more preferably 14% or less, and further preferably 10% or less, 8% or less, 6% or less, 3% or less, and 1% or less in stages as follows.
[0131] <<<BaO>>>
[0132] BaO is a component that improves the meltability of glass and improves the crushability of chemically strengthened glass, and may be contained. When BaO is contained, the content is preferably 0.5% or more, more preferably 1% or more, further preferably 2% or more, particularly preferably 3% or more, and most preferably 5% or more.
[0133] On the other hand, if the content of BaO is too high, the ion exchange performance will be significantly reduced, so it is preferably 20% or less. The content of BaO is more preferably 15% or less, and further preferably 10% or less, 8% or less, 6% or less, 3% or less, and 1% or less in stages as follows.
[0134] <<<ZnO>>>
[0135] ZnO is a component that improves the solubility of glass and may be contained. When ZnO is contained, the content is preferably 0.25% or more, more preferably 0.5% or more.
[0136] On the other hand, if the ZnO content is too high, the durability of the glass will significantly decrease, so it is preferably 20% or less. The ZnO content is more preferably 14% or less, and further preferably 10%, 8%, 6%, 3%, and 1% or less in stages as follows.
[0137] <<<ZrO2>>>
[0138] ZrO2 is a component that improves mechanical strength and chemical durability, and is preferably contained in order to significantly improve CS. The content of ZrO2 when contained is preferably 0.5% or more, more preferably 0.7% or more, further preferably 1.0% or more, particularly preferably 1.2% or more, and most preferably 1.5% or more.
[0139] On the other hand, in order to suppress devitrification during melting, ZrO 2 is preferably 8% or less, more preferably 7.5% or less, further preferably 7% or less, and particularly preferably 6% or less.
[0140] If the content of ZrO2 is too much, the viscosity decreases due to the increase in the devitrification temperature. In order to suppress the deterioration of moldability due to the decrease in viscosity, when the molding viscosity is low, the content of ZrO2 is preferably 5% or less, more preferably 4.5% or less, and further preferably 3.5% or less.
[0141] <<<ZrO2 / R2O>>>
[0142] In order to improve chemical durability, ZrO2 / R2O is preferably 0.02 or more, more preferably 0.04 or more, further preferably 0.06 or more, particularly preferably 0.08 or more, and most preferably 0.1 or more.
[0143] ZrO2 / R2O is preferably 0.2 or less, more preferably 0.18 or less, further preferably 0.16 or less, and particularly preferably 0.14 or less.
[0144] <<<TiO2>>>
[0145] TiO2 is not essential, but when contained, it is preferably 0.05% or more, more preferably 0.1% or more.
[0146] On the other hand, in order to suppress devitrification during melting, the content of TiO2 is preferably 1% or less, more preferably 0.5% or less, and further preferably 0.3% or less.
[0147] <<<SnO2>>>
[0148] SnO2 is not essential, but when contained, it is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, and particularly preferably 2% or more.
[0149] On the other hand, in order to suppress devitrification during melting, the content of SnO2 is preferably 4% or less, more preferably 3.5% or less, further preferably 3% or less, and particularly preferably 2.5% or less.
[0150] <<<Y2O3>>>
[0151] Y2O3 is a component that has the effect of making it difficult for fragments to scatter when chemically strengthened glass is broken, and can be contained. When Y2O3 is contained, the content is preferably 0.3% or more, more preferably 0.5% or more, further preferably 0.7% or more, and particularly preferably 1.0% or more.
[0152] On the other hand, in order to suppress devitrification during melting, the content of Y2O3 is preferably 5% or less, more preferably 4% or less.
[0153] <<<B2O3>>>
[0154] B2O3 is a component that improves the chipping resistance of chemically strengthened glass or chemically strengthened glass and improves its meltability, and may be contained. In order to improve meltability, the content of B2O3 is preferably 0.5% or more, more preferably 1% or more, and further preferably 2% or more.
[0155] On the other hand, if the content of B2O3 is too much, it is easy to produce ribs during melting or phase separation, and the quality of chemically strengthened glass is easy to decrease, so it is preferably 10% or less. The content of B2O3 is more preferably 8% or less, further preferably 6% or less, and particularly preferably 4% or less.
[0156] <<<La2O3+Nb2O5+Ta2O5>>>
[0157] La2O3, Nb2O5 and Ta2O5 are components that make it difficult for fragments of chemically strengthened glass to scatter when broken, and may be contained in order to increase the refractive index.
[0158] When these components are contained, the total content of La2O3, Nb2O5 and Ta2O5 (hereinafter referred to as La2O3+Nb2O5+Ta2O5) is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, and particularly preferably 2% or more.
[0159] In addition, in order to prevent the glass from devitrifying easily during melting, La2O3+Nb2O5+Ta2O5 is preferably 4% or less, more preferably 3% or less, further preferably 2% or less, and particularly preferably 1% or less.
[0160] <<<CeO2>>>
[0161] In addition, CeO 2 may be contained. CeO 2 may suppress coloring by oxidizing the glass. When CeO 2 is contained, the content is preferably 0.03% or more, more preferably 0.05% or more, and further preferably 0.07% or more.
[0162] In order to improve transparency, the content of CeO2 is preferably 1.5% or less, more preferably 1.0% or less.
[0163] <<<Coloring ingredients>>>
[0164] When chemically strengthened glass is colored for use, a coloring component may be added within a range that does not hinder the realization of the desired chemical strengthening characteristics. Examples of coloring components include Co3O4, MnO2, Fe2O3, NiO, CuO, Cr2O3, V2O5, Bi2O3, SeO2, Er2O3, and Nd2O3.
[0165] The content of the coloring components is preferably within a range of 1% or less in total. In order to further increase the visible light transmittance of the glass, it is preferred that these components are substantially not contained.
[0166] <<<HfO2, Nb2O5 and Ti2O3>>>
[0167] In order to improve the weather resistance to ultraviolet light irradiation, HfO2, Nb2O5, and Ti2O3 can be added. When added for the purpose of improving the weather resistance to ultraviolet light irradiation, in order to suppress the influence on other properties, the total content of HfO2, Nb2O5, and Ti2O3 is preferably 1% or less, more preferably 0.5% or less, and more preferably 0.1% or less.
[0168] <<<Clarifying agent>>>
[0169] In addition, as a clarifier during glass melting, SO3, chloride, and fluoride may be appropriately contained. If the total content of the components that function as clarifiers is too much, the strengthening characteristics will be affected. Therefore, it is preferably 2% or less, more preferably 1% or less, and further preferably 0.5% or less, expressed as mass % based on oxides.
[0170] The lower limit is not particularly limited, but is typically preferably 0.05% or more in total, expressed as % by mass based on oxides.
[0171] If the content of SO 3 is too small when SO 3 is used as a clarifier, no effect is observed, so it is preferably 0.01% or more, more preferably 0.05% or more, and even more preferably 0.1% or more, expressed as mass % based on oxides.
[0172] When SO 3 is used as a clarifier, the content of SO 3 is expressed as mass % based on oxides, and is preferably 1% or less, more preferably 0.8% or less, and further preferably 0.6% or less.
[0173] If the Cl content is too high when Cl is used as a clarifier, physical properties such as strengthening characteristics are affected. Therefore, the Cl content is preferably 1% or less, more preferably 0.8% or less, and even more preferably 0.6% or less, expressed as mass % based on oxides.
[0174] When Cl is used as a clarifier, if the Cl content is too small, no effect is observed, so the Cl content is preferably 0.05% or more, more preferably 0.1% or more, and even more preferably 0.2% or more, expressed as mass % based on oxides.
[0175] When SnO 2 is used as a clarifier, the content of SnO 2 is expressed as mass % based on oxide, and is preferably 1% or less, more preferably 0.5% or less, and further preferably 0.3% or less.
[0176] In addition, if the content of SnO2 is too small when using SnO2 as a clarifier, no effect can be seen, so it is preferably 0.02% or more, more preferably 0.05% or more, and further preferably 0.1% or more, expressed as mass % based on oxide.
[0177] <<<P2O5>>>
[0178] The chemically strengthened glass of the first embodiment preferably does not contain P2O5. When P2O5 is contained, it is preferably 2.0% or less, more preferably 1.0% or less, and most preferably not contained.
[0179] In the chemically strengthened glass of the second embodiment, P2O5 is a constituent component of Li3PO4 crystals and is essential. In order to promote crystallization, the content of P2O5 is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, particularly preferably 2% or more, and most preferably 2.5% or more.
[0180] On the other hand, if the P2O5 content is too high, phase separation is likely to occur during melting, and the acid resistance is significantly reduced. Therefore, the P2O5 content is preferably 5% or less, more preferably 4.8% or less, further preferably 4.5% or less, and particularly preferably 4.2% or less.
[0181] <<<As2O3 and Sb2O3>>>
[0182] Preferably, As2O3 is not contained.
[0183] When Sb2O3 is contained, it is preferably 0.3% or less, more preferably 0.1% or less, and most preferably not contained.
[0184] <<Method for measuring glass composition (content of each component)>>
[0185] The glass composition (content of each component) of the chemically strengthened glass and the chemically strengthened glass described later is determined by analysis using an electron probe microanalyzer (EPMA).
[0186] More specifically, as EPMA, JXA-8500F (manufactured by JEOL) was used, and analysis was performed under the following conditions.
[0187] ·Spectral crystal: TAP crystal for Na, Si, Al, P, Sr, Zn, Sn, PETJ crystal for Ca, TAPH crystal for Mg, PETH crystal for K, Zr, Y, Ti, Ba
[0188] Electron beam acceleration voltage: 15kV
[0189] · Irradiation electron beam current: 10nA
[0190] Irradiation acquisition time: 10s at peak position, 5s at background position
[0191] Analysis software used: JEOL software included with the device
[0192] <<Crystal glass>>
[0193] The glass for chemical strengthening may be crystallized glass.
[0194] In the case of crystallized glass, crystallized glass containing one or more crystals selected from the group consisting of lithium silicate crystals, lithium aluminum silicate crystals, zirconium-containing crystals, magnesium-containing crystals, and lithium phosphate crystals is preferred.
[0195] As the lithium silicate crystal, lithium metasilicate crystal, lithium disilicate crystal, or the like is preferable.
[0196] As the lithium phosphate crystal, lithium orthophosphate crystal or the like is preferable.
[0197] As the lithium aluminum silicate crystal, β-quartz solid solution, β-spodumene crystal, petalite crystal, etc. are preferable.
[0198] As the zirconium-containing crystal, zirconium oxide, zirconium oxide solid solution, etc. are preferred. Y, Sn, etc. may be dissolved in the zirconium oxide solid solution.
[0199] As the magnesium-containing crystal, magnesium silicate or the like is preferred.
[0200] In order to improve the mechanical strength, the crystallization rate of the crystallized glass is preferably 10% or more, more preferably 15% or more, further preferably 20% or more, and particularly preferably 25% or more.
[0201] In order to improve transparency, the ratio is preferably 70% or less, more preferably 60% or less, and particularly preferably 50% or less. A small crystallinity is also excellent in that it is easy to bend and mold by heating.
[0202] The crystallinity can be calculated from the X-ray diffraction intensity by the Rietveld method.
[0203] The Rietveld method is described in the "Crystallization Analysis Handbook" edited by the Editorial Committee of the "Crystallization Analysis Handbook" of the Japan Crystallography Society (Kyoritsu Publishing, 1999, pp. 492-499).
[0204] <<Method for producing chemically strengthened glass>>
[0205] As a method for producing chemically strengthened glass, glass raw materials are appropriately prepared so as to obtain glass of a desired composition, and after heating and melting in a glass melting furnace, the glass is homogenized by bubbling, stirring, adding a clarifier, etc., and then formed into a glass plate of a predetermined thickness, and slowly cooled. Alternatively, the glass can be formed into a plate by a method of forming a block, slowly cooling, and then cutting.
[0206] As a method for forming into a plate shape, for example, a float process, a press process, a fusion process, and a down-draw process can be cited. In particular, when a large glass plate is manufactured, a float process is preferred. In addition, continuous forming methods other than the float process, such as a fusion process and a down-draw process, can be cited. In order to form into a flat plate shape by the glass forming method as described above, the chemically strengthened glass of this embodiment preferably has a liquidus viscosity of 130 dPa·s or more.
[0207] The chemically strengthened glass of the present embodiment is usually formed into a plate shape, and may be a flat plate or a glass plate subjected to bending processing.
[0208] <Chemically strengthened glass>
[0209] <<Glass composition>>
[0210] In the present embodiment, the glass composition of the chemically strengthened glass is the glass composition of a portion deeper than the compressive stress layer depth of the chemically strengthened glass, and is the same as the composition of the chemically strengthened glass except for the case where an extreme ion exchange treatment is performed.
[0211] That is, in the chemically strengthened glass of the first embodiment, the mother composition of the chemically strengthened glass, expressed in mol % based on oxides, preferably contains 52 to 75% SiO2, 1 to 20% Al2O3, 1 to 20% Na2O, and 1 to 20% Li2O.
[0212] In the chemically strengthened glass of the second embodiment, the matrix composition of the chemically strengthened glass is preferably a composition containing 40 to 70% of SiO 2 , 10 to 35% of Li 2 O, and 1 to 15% of Al 2 O 3 , expressed in mol % based on oxides.
[0213] <<Plate thickness>>
[0214] The thickness of the chemically strengthened glass of this embodiment is greater than 2 mm, preferably greater than 2.5 mm, more preferably greater than 3 mm, further preferably greater than 4 mm, and particularly preferably greater than 5 mm. When the thickness is greater than 2 mm, the strength is increased and excellent anti-flying stone property is exhibited.
[0215] From the viewpoint of achieving weight reduction, the plate thickness is preferably 7 mm or less, more preferably 6.6 mm or less, further preferably 6.2 mm or less, and particularly preferably 5.8 mm or less.
[0216] <<Method for producing chemically strengthened glass>>
[0217] <<<Process A>>>
[0218] The method for producing chemically strengthened glass according to the present embodiment includes a step of bringing an inorganic salt composition containing 0.1 mass % or more of a lithium inorganic salt into contact with a chemically strengthened glass having a thickness greater than 2 mm (hereinafter also referred to as step A).
[0219] In step A, a chemical strengthening treatment (ion exchange treatment) is performed.
[0220] Chemical strengthening treatment is a treatment in which an inorganic salt composition is brought into contact with glass to replace metal ions in the glass with metal ions in the inorganic salt composition having an ion radius larger than that of the metal ions in the glass, thereby forming a compressive stress layer on the surface of the glass.
[0221] As a method for contacting glass with an inorganic salt composition, there can be mentioned a method of applying a paste-like inorganic salt composition to glass, a method of spraying an aqueous solution of an inorganic salt composition to glass, a method of immersing glass in an inorganic salt composition (also referred to as "molten salt") heated to a melting point or above, etc. Among these, from the viewpoint of improving productivity, a method of immersing glass in a molten inorganic salt composition (molten salt) is preferred.
[0222] In this specification, the "inorganic salt composition" means a composition containing an inorganic salt.
[0223] Examples of the inorganic salt contained in the inorganic salt composition include nitrates, sulfates, carbonates, chlorides and the like.
[0224] Examples of the nitrate include lithium nitrate, sodium nitrate, potassium nitrate, cesium nitrate, rubidium nitrate, and silver nitrate.
[0225] Examples of the sulfate include lithium sulfate, sodium sulfate, potassium sulfate, cesium sulfate, rubidium sulfate, and silver sulfate.
[0226] Examples of the carbonate include lithium carbonate, sodium carbonate, potassium carbonate, cesium carbonate, rubidium carbonate, and silver carbonate.
[0227] Examples of the chloride include lithium chloride, sodium chloride, potassium chloride, cesium chloride, rubidium chloride, and silver chloride.
[0228] They can be used alone or in combination.
[0229] The main component of the inorganic salt composition is preferably a nitrate, more preferably sodium nitrate or potassium nitrate. Here, the "main component" refers to a component whose content in the inorganic salt composition is 80% by mass or more.
[0230] Examples of the lithium-containing inorganic salt include lithium nitrate, lithium sulfate, lithium carbonate, and lithium chloride, and these may be used alone or in combination of two or more.
[0231] Among these, lithium nitrate is preferred as the lithium-containing inorganic salt.
[0232] The content of the lithium-containing inorganic salt refers to the ratio of the mass of the lithium-containing inorganic salt to the total weight of the inorganic salt composition.
[0233] The content of the lithium-containing inorganic salt in the inorganic salt composition is 0.1 mass % or more, preferably 1 mass % or more, more preferably 2 mass % or more, further preferably 3 mass % or more, particularly preferably 4 mass % or more, and most preferably 6 mass % or more.
[0234] On the other hand, the content of the lithium-containing inorganic salt in the inorganic salt composition is preferably 20 mass % or less, more preferably 18 mass % or less, further preferably 16 mass % or less, particularly preferably 14 mass % or less, and most preferably 12 mass % or less.
[0235] The inorganic salt composition in step A may contain other inorganic salts in addition to the lithium-containing inorganic salt. Examples of other inorganic salts include potassium carbonate, potassium sulfate, potassium chloride, sodium nitrate, sodium carbonate, sodium sulfate, and sodium chloride. Among these, sodium nitrate is preferred.
[0236] In the above-mentioned step A using the inorganic salt composition, for example, lithium ions in the glass are exchanged with sodium ions in the inorganic salt composition, and at the same time, sodium ions in the glass are exchanged with potassium ions in the inorganic salt composition.
[0237] In the inorganic salt composition of step A, silicic acid may be added as a pH lowering agent.
[0238] When an inorganic salt composition containing nitrate is heated at high temperature for a long time, the nitrate decomposes, thereby increasing the pH of the molten inorganic salt composition (molten salt). - The glass network is cut off by the reaction and the appearance of the glass surface is poor. If silicic acid is added, the increase of pH can be suppressed by the neutralization effect. As silicic acid, silica gel or metasilicic acid is particularly preferred.
[0239] In the step A, the temperature of the inorganic salt composition in contact with the glass for chemical strengthening is preferably 360° C. or higher, more preferably 370° C. or higher, further preferably 380° C. or higher, particularly preferably 390° C. or higher.
[0240] In addition, from the viewpoint of improving stone flying resistance, ball falling strength and scratch resistance while maintaining the appearance quality after ion exchange, the temperature of the inorganic salt composition is preferably 500°C or less, more preferably 480°C or less, further preferably 465°C or less, and particularly preferably 455°C or less.
[0241] In step A, the time (contact time) for which the chemically strengthened glass is brought into contact with the inorganic salt composition is, for example, 24 hours or more, preferably 25 hours or more, more preferably 36 hours or more, further preferably 48 hours or more, and particularly preferably 60 hours or more, from the viewpoint of increasing the surface compressive stress value.
[0242] From the viewpoint of improving the flystone resistance and safety, the contact time is preferably 200 hours or less, more preferably 150 hours or less, further preferably 120 hours or less, and particularly preferably 100 hours or less.
[0243] The chemical strengthening treatment (ion exchange treatment) in step A may be a one-step treatment or may be a two-step or more treatment (multi-step strengthening treatment) performed under different conditions.
[0244] When a multi-stage strengthening treatment is performed, an inorganic salt composition containing 0.1 mass % or more of the lithium-containing inorganic salt may be used in any of the first stage or the second and subsequent ion exchange treatments.
[0245] When a multi-step strengthening treatment is performed in step A, the method for producing a chemically strengthened glass according to the present embodiment may include, after step A, a step of heating the glass for chemical strengthening (hereinafter also abbreviated as step B).
[0246] <<<Process B>>>
[0247] The step B is a step of heating the chemically strengthened glass to a heating temperature of 100° C. or higher without contacting the glass with the inorganic salt composition.
[0248] The heating temperature is more preferably 200° C. or higher, and further preferably 300° C. or higher.
[0249] For the sake of work efficiency and prevention of deformation of the chemically strengthened glass, the heating temperature is preferably 500° C. or lower.
[0250] The heating time in step B is preferably 0.5 hours or longer, more preferably 1 hour or longer, and even more preferably 2 hours or longer.
[0251] From the viewpoint of work efficiency, the heating time in step B is preferably 12 hours or less.
[0252] <<<Preheating process>>>
[0253] The method for producing the chemically strengthened glass according to the present embodiment may include a preheating step of heating the glass for chemical strengthening before performing the step A.
[0254] The preheating step is a step of heating the chemically strengthened glass to a preheating temperature of 100° C. or higher without contacting the inorganic salt composition. The preheating temperature is preferably 150° C. or higher, more preferably 200° C. or higher, and further preferably 300° C. or higher.
[0255] On the other hand, in order to prevent deformation of the chemically strengthened glass, the preheating temperature is preferably 500° C. or lower.
[0256] From the viewpoint of sufficiently stably heating, the heating time in the preheating step is preferably 10 minutes or longer, more preferably 30 minutes or longer, and even more preferably 1 hour or longer.
[0257] From the viewpoint of work efficiency, the heating time in the preheating step is preferably 5 hours or less.
[0258] <<Stress distribution>>
[0259] <<<DOC>>>
[0260] In the present embodiment, the compressive stress layer depth DOC of the chemically strengthened glass is 500 μm or more, preferably 550 μm or more, more preferably 600 μm or more, and particularly preferably 650 μm or more, for the reason of exhibiting excellent flystone resistance.
[0261] For the same reason, the DOC is 1500 μm or less, preferably 1400 μm or less, more preferably 1300 μm or less, further preferably 1200 μm or less, and particularly preferably 1100 μm or less.
[0262] <<<DOC / 1000t>>>
[0263] In the present embodiment, for the reason that the flying stone resistance is better, when the thickness of the chemically strengthened glass is set to t (unit: mm), the ratio of the depth of the compressive stress layer DOC to 1000t (the unit of the plate thickness converted from mm to μm) (DOC / 1000t) is preferably 0.15 or more, more preferably 0.16 or more, further preferably 0.18 or more, and particularly preferably 0.20 or more.
[0264] For the same reason, the ratio of DOC to 1000 t (DOC / 1000 t) is preferably 0.30 or less, more preferably 0.27 or less, further preferably 0.25 or less, particularly preferably 0.24 or less, and most preferably 0.23 or less.
[0265] <<<DOL 50 >>>
[0266] In the chemically strengthened glass of the present embodiment, the depth DOL when the compressive stress value is 50 MPa is50 It is preferably 200 μm or more, more preferably 280 μm or more, and further preferably 350 μm or more.
[0267] On the other hand, DOL 50 It is preferably 600 μm or less, more preferably 550 μm or less, and further preferably 500 μm or less.
[0268] <<<CTmax>>>
[0269] In the present embodiment, the maximum value CTmax of the tensile stress of the chemically strengthened glass is 20 MPa or more, preferably 25 MPa or more, and more preferably 30 MPa or more, for the reasons of excellent stone flying resistance, falling ball strength, and scratch resistance.
[0270] From the viewpoint of excellent safety, CTmax is 59 MPa or less, preferably 55 or less, and more preferably 50 MPa or less.
[0271] (CTA)
[0272] The maximum value CTmax of the tensile stress is equal to or less than CTA (unit: MPa) represented by the following formula (1).
[0273] In the following formula (1), t represents the plate thickness of the chemically strengthened glass (unit: mm), and ln(t) represents the natural logarithm with e as the base.
[0274] By keeping CTmax below CTA, it is possible to avoid exceeding the CT limit, ensure safety, and maximize DOC.
[0275] From the viewpoint of further avoiding exceeding the CT limit, the value obtained by subtracting the CTmax value from the CTA value is preferably 1 MPa or more, more preferably 3 MPa or more, and even more preferably 5 MPa or more.
[0276] CTA=-36.2ln(t)+97.7…(1)
[0277] <<<CTave>>>
[0278] In the chemically strengthened glass of the present embodiment, the average value CTave of the tensile stress is preferably 10 MPa or more, more preferably 15 MPa or more, and further preferably 20 MPa or more.
[0279] On the other hand, CTave is preferably 60 MPa or less, more preferably 55 or less, and further preferably 50 MPa or less.
[0280] The average value of the tensile stress CTave is the average value of the tensile stress in a region deeper than the compressive stress layer depth DOC.
[0281] <<<CS0>>>
[0282] <<<<CS0(SLP)>>>>
[0283] In the present embodiment, from the viewpoint of achieving a balance between compressive stress and tensile stress, the surface compressive stress value CS0(SLP) of the chemically strengthened glass measured by SLP is preferably 200 MPa or less, more preferably 170 MPa or less, further preferably 150 Pa or less, and particularly preferably 120 MPa or less.
[0284] On the other hand, from the viewpoint of improving the bending strength, CS0(SLP) is preferably 50 MPa or more, more preferably 70 MPa or more, and further preferably 90 MPa or more.
[0285] <<<<CS0(FSM)>>>>
[0286] In the present embodiment, the surface compressive stress value CS0 (FSM) from K ions of the chemically strengthened glass subjected to two or more stages of chemical strengthening treatment measured by FSM is preferably 1400 MPa or less, more preferably 1200 MPa or less, further preferably 1000 Pa or less, and particularly preferably 800 MPa or less.
[0287] On the other hand, from the viewpoint of improving the bending strength, CS0 (FSM) is preferably 50 MPa or more, more preferably 70 MPa or more, and further preferably 90 MPa or more.
[0288] <<<CS 10 >>>
[0289] In this embodiment, the compressive stress value CS of the chemically strengthened glass at a depth of 10 μm from the surface is 10 It is preferably 200 MPa or less, more preferably 180 MPa or less, and further preferably 150 MPa or less.
[0290] On the other hand, from the perspective of improving bending strength, CS 10 It is preferably 50 MPa or more, more preferably 70 MPa or more, and further preferably 90 MPa or more.
[0291] <<<CS 400 >>>
[0292] In the chemically strengthened glass of the present embodiment, the compressive stress value CS at a depth of 400 μm from the surface is 400 It is preferably 30 MPa or more, more preferably 35 MPa or more, and further preferably 40 MPa or more.
[0293] On the other hand, the compressive stress value CS 400 It is preferably 100 MPa or less, preferably 85 MPa or less, and preferably 70 MPa or less.
[0294] <<<CS 500 >>>
[0295] In the chemically strengthened glass of the present embodiment, the compressive stress value CS at a depth of 500 μm from the surface is 500 It is preferably 15 MPa or more, more preferably 25 MPa or more, and further preferably 35 MPa or more.
[0296] Compressive stress value CS 500 It is preferably 80 MPa or less, more preferably 70 MPa or less, and further preferably 60 MPa or less.
[0297] <<<CS 600 >>>
[0298] In the chemically strengthened glass of the present embodiment, the compressive stress value CS at a depth of 600 μm from the surface is 600 It is preferably 0 MPa or more, more preferably 10 MPa or more, and further preferably 20 MPa or more.
[0299] On the other hand, the compressive stress value CS 600 It is preferably 50 MPa or less, more preferably 45 MPa or less, and further preferably 40 MPa or less.
[0300] <<<CS 400 / CS 10 >>>
[0301] In the chemically strengthened glass of this embodiment, the compressive stress value CS 400 and compressive stress value CS 10 The ratio (CS 400 / CS 10 ) is preferably 0.30 or more, more preferably 0.40 or more, and further preferably 0.50 or more.
[0302] On the other hand, compared with (CS 400 / CS 10 ) is preferably 0.80 or less, more preferably 0.75 or less, and further preferably 0.70 or less.
[0303] <<<CS 600 / CS 10 >>>
[0304] In the chemically strengthened glass of this embodiment, the compressive stress value CS 600and compressive stress value CS 10 The ratio (CS 600 / CS 10 ) is preferably 0.04 or more, more preferably 0.10 or more, and further preferably 0.18 or more.
[0305] On the other hand, compared with (CS 600 / CS 10 ) is preferably 0.50 or less, more preferably 0.45 or less, and further preferably 0.40 or less.
[0306] <<<ICS>>>
[0307] In the chemically strengthened glass of the present embodiment, from the viewpoint of achieving a balance between compressive stress and tensile stress, the integrated value ICS in the plate thickness direction of the compressive stress value from the surface to the depth position where the compressive stress value is zero is preferably 25000 MPa·μm or more, more preferably 30000 MPa·μm or more, and further preferably 34000 MPa·μm or more.
[0308] On the other hand, from the perspective of excellent safety, the ICS is preferably 47000 MPa·μm or less, more preferably 46000 MPa·μm or less, and further preferably 45000 MPa·μm or less.
[0309] <<<ICS 400 >>>
[0310] In the chemically strengthened glass of the present embodiment, the integral value ICS in the thickness direction of the compressive stress value from the position of the depth of 400 μm to the depth position where the compressive stress value is zero is 400 It is preferably 3000 MPa·μm or more, more preferably 5000 MPa·μm or more, and further preferably 7000 MPa·μm or more.
[0311] On the other hand, ICS 400 It is preferably 60,000 MPa·μm or less, more preferably 55,000 MPa·μm or less, and further preferably 50,000 MPa·μm or less.
[0312] <<<ICS 400 / ICS>>>
[0313] In the chemically strengthened glass of this embodiment, ICS 400 The ratio of the integrated value ICS of the compressive stress value in the plate thickness direction from the surface to the depth position where the compressive stress value is zero (ICS 400 / ICS) is preferably 0.13 or more, more preferably 0.20 or more, and further preferably 0.28 or more.
[0314] On the other hand, compared with (ICS 400 / ICS) is preferably 0.90 or less, more preferably 0.85 or less, and further preferably 0.80 or less.
[0315] <<<Deep Slope>>>
[0316] In the chemically strengthened glass of the present embodiment, the depth slope is preferably -0.01 or less, more preferably -0.05 or less, and further preferably -0.10 or less.
[0317] On the other hand, the deep slope is preferably not less than -0.25, more preferably not less than -0.22, and further preferably not less than -0.20.
[0318] The deep slope of chemically strengthened glass is CS obtained using SLP 50 The ratio (CS) to the value obtained by subtracting 50 from DOC (DOC-50) 50 / (DOC-50)).
[0319] <<<Surface slope>>>
[0320] In the chemically strengthened glass of the present embodiment, the skin slope is preferably 400 or less, more preferably 350 or less, and even more preferably 300 or less.
[0321] On the other hand, the skin slope is preferably 100 or more, more preferably 150 or more, and even more preferably 200 or more.
[0322] The surface slope of chemically strengthened glass is the ratio of CS0 to DOL (CS0 / DOL) obtained using FSM.
[0323] Here, DOL is the depth of the compressive stress layer derived from potassium ions (unit: μm) obtained using FSM.
[0324] <<Crack Occurrence Rate>>
[0325] The crack generation rate of the chemically strengthened glass of the present embodiment, evaluated by the strength test method according to ISO 20567-1 test method A, is preferably 20% or less, more preferably 18% or less, further preferably 15% or less, and particularly preferably 13% or less. When the crack generation rate is 20% or less, the flystone resistance can be more effectively improved. When the crack generation rate is calculated, n is 3 or more.
[0326] The crack generation rate of the chemically strengthened glass of the present embodiment, as evaluated by the strength test method according to SAE J400, is preferably 40% or less, more preferably 30% or less, further preferably 20% or less, and particularly preferably 13% or less. When the crack generation rate is 40% or less, the flystone resistance can be more effectively improved. When the crack generation rate is calculated, n is 3 or more.
[0327] <<Application>>
[0328] As an application of the chemically strengthened glass of this embodiment, for example, a protective component of a sensor can be cited. As a sensor, for example, a sensor mounted on a mobile device such as a car or a drone; an outdoor sensor; a sensor mounted on a surveillance camera, etc. can be cited.
[0329] The chemically strengthened glass of the present embodiment is preferably used as a protective member for a sensor mounted on a mobile device, and more preferably used as a protective member for a vehicle-mounted sensor, among these, from the viewpoint of exhibiting excellent flystone resistance.
[0330] Figure 1 (a) and Figure 1 (b) is a perspective view showing a configuration example in which chemically strengthened glass is used as a protective member.
[0331] Figure 1 In (a), chemically strengthened glass is used as the cover 10 of the cylindrical protective member 1 that accommodates the sensor 20 (including the camera 30) attached to the attachment portion 5.
[0332] In the protection member 1 , the support portion 2 that supports the cover portion 10 may be made of chemically strengthened glass, but may also be made of metal such as stainless steel or alumite.
[0333] Figure 1 In (b), chemically strengthened glass is used as the hemispherical protective member 1 that accommodates the sensor 20 mounted on the mounting portion 5 .
[0334] The shape of the protection member 1 is not limited to the cylindrical shape and the hemispherical shape, and other shapes include a cylindrical shape, a prism shape, a hemispherical polyhedron shape, and the like.
[0335] The protective member 1 can be formed by bonding a plurality of chemically strengthened glasses together.
[0336] For example, in Figure 1 In (a), when chemically strengthened glass is used not only for the cover 10 but also for the support 2, an adhesive layer may be formed between the cover 10 and the support 2 to bond the two.
[0337] Example
[0338] Hereinafter, the present invention will be described with reference to Examples, but the present invention is not limited thereto.
[0339] Hereinafter, Examples 1 to 5 are embodiments, Examples 6 to 12 are comparative examples, and Example 13 is a reference example.
[0340] <Production of chemically strengthened glass>
[0341] Glass raw materials were prepared so that the glass composition expressed in mol % based on oxides would be the following composition, and weighed to give 400 g to prepare glass.
[0342] Next, the mixed raw materials are placed in a platinum crucible and put into an electric furnace at 1500 to 1700° C. to be melted for about 3 hours, degassed, and homogenized, thereby obtaining molten glass.
[0343] The obtained molten glass was poured into a mold, kept at a temperature near the glass transition temperature (714° C.) for about 1 hour, and then cooled to room temperature at a rate of 100° C. / min to obtain a glass block.
[0344] From the obtained glass blocks, glass plates (chemically strengthened glass A or B) having a plate thickness (unit: mm)×50 mm×50 mm as shown in Table 1 below were prepared.
[0345] <<Chemical Strengthening Glass A>>
[0346] SiO2: 66.2%, Al2O3: 11.2%, MgO: 3.1%, CaO: 0.2%, ZrO2: 1.3%, Y2O3: 0.5%, Li2O: 10.4%, Na2O: 5.6%, K2O: 1.5%
[0347] <<Chemical Strengthening Glass B>>
[0348] SiO2: 64.2%, Al2O3: 8.0%, MgO: 10.5%, CaO: 0.1%, SrO: 0.1%, BaO: 0.1%, ZrO2: 0.5%, Na2O: 12.5%, K2O: 4.0%
[0349] The glass compositions of the obtained glass plates (chemically strengthened glasses A and B) were determined by the above method and the results were consistent with the above compositions. The value obtained by subtracting the total content of each component from 100% was defined as the content of Li (Li2O).
[0350] <Production of chemically strengthened glass>
[0351] The glass plate obtained above was subjected to a chemical strengthening treatment by immersing the glass plate in a molten salt composition under the conditions shown in Table 1 below (step A).
[0352] In addition, in Example 3, two steps of chemical strengthening treatment were performed.
[0353] In any of the examples, the glass sheet was heated at a preheating temperature of 350° C. for 15 minutes before the chemical strengthening treatment (preheating step).
[0354] In Example 13, the chemically strengthened glass A was used as it is without being subjected to chemical strengthening treatment.
[0355] <Evaluation of chemically strengthened glass>
[0356] The chemically strengthened glass obtained was subjected to various evaluations. In Table 1 below, "-" indicates that no evaluation was performed, and the case where no measurement could be performed was recorded as 0.
[0357] <<Measurement of stress distribution>>
[0358] The stress of the chemically strengthened glass was measured using a scattered light photoelastic stress meter (SLP-2000 manufactured by Orihara Seisakusho Co., Ltd.) by the method described in International Publication No. 2018 / 056121. In addition, the stress distribution was calculated using the attached software [SlpV+Ver.2021.07.13.001] of the scattered light photoelastic stress meter.
[0359] Among them, in Example 3 in which two stages of chemical strengthening treatment were performed, the stress of the chemically strengthened glass was measured using a glass surface stress meter (FSM6000-UV manufactured by Orihara Manufacturing Co., Ltd.) by the method described in International Publication No. 2018 / 056121.
[0360] The function used to obtain the stress distribution is σ(x)=[a1×erfc(a2×x)+a3×erfc(a4×x)+a5]. i (i=1-5) is the fitting parameter, and erfc is the complementary error function. The complementary error function is defined by the following formula.
[0361]
[0362] In the evaluation of this specification, the fitting parameters are optimized by minimizing the residual sum of squares between the obtained raw data and the above function. The measurement processing condition is single, the edge method is selected in the surface specification, 6.0μm is selected in the internal surface end specification, automatic is selected in the internal left and right end specification, automatic is selected in the internal deep end specification (sample film thickness center), and the extension specification of the phase curve to the sample thickness center is selected as the fitting curve.
[0363] From the obtained stress distribution, various parameters such as the depth of the compressive stress layer DOC and the maximum value of the tensile stress CTmax were determined. The results are shown in Table 1 below.
[0364] <<Flying stone resistance>>
[0365] <<<Crack Occurrence Rate (ISO)>>>
[0366] According to the strength test method of ISO 20567-1 Test Method A, a flying stone test was carried out under the following conditions, and the crack generation rate (n=10) was calculated. The results are shown in Table 1 below.
[0367] Chilled Iron Grit
[0368] Stone size: 3.55~5mm
[0369] Injection volume: 500g
[0370] Injection pressure: 100kPa
[0371] Sample setting angle: 54°
[0372] ·Injection time: 8~12s
[0373] Number of shots: 2
[0374] Sample collision area: 40mm×40mm
[0375] <<<Crack occurrence rate (SAE)>>>
[0376] According to the strength test method of SAE J400, a flying stone test was carried out under the following conditions, and the crack generation rate (n=5) was calculated. The results are shown in Table 1 below.
[0377] ·Flying stones: river gravel
[0378] Stone size: 5-13mm
[0379] Injection volume: 0.473L
[0380] Injection pressure: 0.483MPa
[0381] Sample setting angle: 90°
[0382] ·Ejection time: 10s
[0383] Number of shots: 1
[0384] Sample collision area: 40mm×40mm
[0385] The crack occurrence rate (unit: %) was calculated as follows.
[0386] Crack generation rate: 100×(number of samples with cracks in the flying stone test / total number of evaluation samples)
[0387] · Determination of sample cracks: After the flying stone test, cracks extending beyond the range of each scratch exist on the surface of the sample.
[0388] <<Safety (Crack Behavior)>>
[0389] The crack behavior of the chemically strengthened glass was evaluated as follows using a superhard automatic punch manufactured by TRUSCO.
[0390] Figure 2 It is a schematic diagram for explaining the evaluation method of crack behavior.
[0391] like Figure 2 As shown, a superhard automatic punch 410 is provided at the center of the surface 210 of the 50 mm×50 mm chemically strengthened glass 200 disposed on a test stand 400 and is pressed vertically into the crack of the chemically strengthened glass 200 under static load conditions.
[0392] If the chemically strengthened glass did not break, the above operation was repeated while increasing the load by 1 kgf intervals until cracking. In the following Table 1, the case where the number of broken pieces of the chemically strengthened glass when cracking is 2 to 9 is recorded as "◎", the case where it is 10 to 19 is recorded as "○", and the case where it is 20 or more is recorded as "×".
[0393] The smaller the number of breakages, the better the safety can be evaluated.
[0394] [Table 1]
[0395]
[0396] <Summary of evaluation results>
[0397] As shown in Table 1, Examples 1 to 5 exhibited excellent flying stone resistance compared to Examples 8 to 13. In addition, Examples 1 to 5 exhibited excellent cracking behavior (that is, excellent safety) compared to Examples 6 to 8 and Examples 11 to 12.
Claims
1. A chemically strengthened glass having a plate thickness greater than 2 mm, a compressive stress layer depth DOC of 500 to 1500 μm, and a maximum tensile stress CTmax of 20 to 59 MPa.
2. The chemically strengthened glass according to claim 1, wherein: When the plate thickness is t, the maximum value CTmax of the tensile stress is less than or equal to CTA calculated by the following formula (1), and the unit of t is mm. CTA=-36.2ln(t)+97.7…(1).
3. The chemically strengthened glass according to claim 1, wherein: The surface compressive stress value CS0 is 1400 MPa or less.
4. The chemically strengthened glass according to claim 1, wherein: Compressive stress value CS at a depth of 10 μm from the surface 10 Below 200MPa.
5. The chemically strengthened glass according to claim 1, wherein: Depth DOL when the compressive stress value is 50MPa 50 200~600μm.
6. The chemically strengthened glass according to claim 1, wherein: Compressive stress value CS at a depth of 400 μm from the surface 400 It is 30~100MPa.
7. The chemically strengthened glass according to claim 1, wherein: Compressive stress value CS at a depth of 500 μm from the surface 500 It is 15~80MPa.
8. The chemically strengthened glass according to claim 1, wherein: Compressive stress value CS at a depth of 600 μm from the surface 600 0~50MPa.
9. The chemically strengthened glass according to claim 1, wherein: Compressive stress value CS at a depth of 400 μm from the surface 400 The compressive stress value CS at a depth of 10 μm from the surface 10 CS 400 / CS 10 It is 0.30~0.
80.
10. The chemically strengthened glass according to claim 1, wherein: Compressive stress value CS at a depth of 600 μm from the surface 600 The compressive stress value CS at a depth of 10 μm from the surface 10 CS 600 / CS 10 It is 0.04~0.
50.
11. The chemically strengthened glass according to claim 1, wherein: The deep slope is -0.25 to -0.
01.
12. The chemically strengthened glass according to claim 1, wherein: When the plate thickness is t, a ratio of the compressive stress layer depth DOC to 1000t DOC / 1000t is 0.15 to 0.30, and the unit of t is mm.
13. The chemically strengthened glass according to claim 1, wherein: ICS is the integral value of the compressive stress value in the plate thickness direction from the position with a depth of 400 μm to the depth position where the compressive stress value is zero. 400 It is 3000~60000MPa·μm.
14. The chemically strengthened glass according to claim 1, wherein: ICS is the integral value of the compressive stress value in the plate thickness direction from the position with a depth of 400 μm to the depth position where the compressive stress value is zero. 400 Ratio ICS to the integrated value ICS of the compressive stress value in the plate thickness direction from the surface to the depth position where the compressive stress value is zero 400 / ICS is 0.13~0.
90. The chemically strengthened glass according to claim 1 , which is lithium-containing aluminosilicate glass.
16. The chemically strengthened glass according to claim 1, wherein: Expressed as mol% based on oxides, it contains 52 to 75% SiO2, 1 to 20% Al2O3, 1 to 20% Na2O, and 1 to 20% Li2O.
17. The chemically strengthened glass according to claim 1, wherein: The crack generation rate evaluated by the strength test method according to ISO 20567-1 Test Method A is 20% or less.
18. The chemically strengthened glass according to claim 1, wherein: The crack generation rate evaluated according to the strength test method of SAE J400 is 20% or less.
19. The chemically strengthened glass according to claim 1, which is used as a protective member for an in-vehicle sensor.
20. A method for producing a chemically strengthened glass, the method being a method for producing the chemically strengthened glass according to any one of claims 1 to 19, An inorganic salt composition containing a lithium inorganic salt in an amount of 0.1 mass % or more is brought into contact with a chemically strengthened glass having a thickness of more than 2 mm.
21. The method for producing chemically strengthened glass according to claim 20, wherein: The inorganic salt composition and the chemically strengthened glass are allowed to contact with each other for 25 hours or longer.
22. The method for producing chemically strengthened glass according to claim 20, wherein: Before the inorganic salt composition is brought into contact with the chemically strengthened glass, the chemically strengthened glass is preheated.
23. The method for producing chemically strengthened glass according to claim 20, wherein: In the inorganic salt composition, the content of lithium nitrate is 1% by mass or more, and the content of sodium nitrate is 80% by mass or more.
Citation Information
Patent Citations
remote control device
CS100301B1
a device for adjusting feeds in machine tools, especially horizontal boring machines
CS100304B1
Surface refractive index measuring method, and surface stress measuring method employing same
WO2017115811A1
Stress measuring device for tempered glass, stress measuring method for tempered glass, method for manufacturing tempered glass, and tempered glass
WO2018056121A1
Sensor module and protective glass
WO2019009336A1